Cosmopolitismo e cidadania. Karl Popper: uma leitura moderna do Menexeno de Platão - Colen, J. A. (2015)
In Plato’s dialogue, Menexenus, a kind of complementary piece to the Gorgias, Socrates shows the power of “harmful” rhetoric by example, in the composition of a funeral oration. In a famous modern reading, Karl Popper accuses Plato of writing a devastating parody of Pericles’ Funeral Oration, a cornerstone in the memory of Athenian democracy, proffered half a century before the drafting of the Republic. Pericles who, according to Popper, is not innocent of some populist concessions belongs to the group of defenders of “egalitarian individualism”, typical of the Great Generation,« and his speech conveys a political program that we cherish. Pericles is aware that democracy is not limited to the mere principle that ‘the people shall govern’, but must be based on reason and faith in human kindness. There is much to say about Popper’s reading of Plato dialogues, but he certainly does not ignore the Platonic political dimension. This paper, which introduces the first Portuguese translation of the dialogue, emphasizes the paradoxical nature of the relationship between democratic politics and rhetoric since the enlightenment and directs our attention to a platonic theme: autochthony and citizenship.